Reflections on task-based language teaching - Ellis, Rod (Bristol ; Blue Ridge Summit, PA : Multilingual Matters, 2018)
'This book discusses whether task-based language teaching is appropriate for all learners in all instructional contexts. Chapters cover both research and pedagogy and draw on the author's experience of working with teachers to suggest ways of addressing the problems they often face with task-based language teaching'--
A brief history of task-based language teaching and research -- Task-based research and language pedagogy -- Non-reciprocal tasks, comprehension and second language acquisition -- Focus on form : a critical review -- Preparing learners to perform tasks -- Is there a role for explicit instruction in task-based language teaching? -- Measuring second language learners : performance of tasks -- Task-based language pedagogy -- Task-based language teaching : sorting out the misunderstandings -- Moving task-based language teaching forward -- Towards a modular curriculum -- An options-based approach to doing task-based language teaching -- Teachers evaluating tasks -- Key issues in task-based research and pedagogy.
Includes bibliographical references and index.
Keywords: Language and languages -- Study and teaching; Language teachers -- Training of